The variation of FiO2 with circuit type and peak inspiratory flow rate during non-invasive respiratory support using domiciliary ventilators and its significance during the COVID-19 pandemic. (May 2022) - Messer, Ben; Tedd, Hilary; Doris, Tom; Mountain, Andrew; Gatilogo, Cris; Sovani, Milind
Background: The COVID-19 pandemic has resulted in increased admissions with respiratory failure and there have been reports of oxygen failure and shortages of machines to deliver ventilation and Continuous Positive Airway Pressure (CPAP). Domiciliary ventilators which entrain room air have been widely used during the pandemic. Poor outcomes reported with non-invasive respiratory support using ventilators which lack an oxygen blender could be related to an unreliable Fraction of inspired O2 (FiO2 ). Additionally, with concerns about oxygen failure, the variety of ventilator circuits used as well as differing peak inspiratory flow rates (PIFR) could impact on the FiO2 delivered during therapy with domiciliary ventilators. Methods: In a series of bench tests, we tested the effect of choice of circuit and different PIFR on the FiO2 achieved during simulation of ventilation and CPAP therapy using domiciliary ventilators. Results: FiO2 was highly dependent upon the type of circuit used with circuits with an active exhalation valve achieving similar FiO2 at lower oxygen flow rates than circuits using an exhalation port. During CPAP therapy, high PIFR resulted in significantly lower FiO2 than low PIFR. Conclusions: This study has implications for oxygen usage as well as delivery of non-invasive respiratory support during therapy with domiciliary ventilators when these are used during the second wave of COVID-19.